Successful rearing of a young Egyptian Vulture Neophron percnopterus by a single male after the death of his mate (Avocetta, 2025)
The Egyptian Vulture Neophron percnopterus is critically endangered in Italy, with only 11-14 pairs censused in recent years, most of them in Sicily. Urgent conservation actions are therefore needed to prevent any mortality and increase the productivity of each pair. Here we present a case of supplementary feeding carried out in Sicily to sustain a breeding adult male Egyptian Vulture that lost his mate after hatching on May 19, 2023. The single male took advantage of the supplementary feeding right from the beginning and raised a chick until it fledged on July 26. He also formed a pair with a new adult female that was attracted by the food we provided. The new female showed aggressive behaviour towards the young immediately after fledging. However, five days after fledgling, the young was observed flying alongside the adults, suggesting that the breeding was successful.
Keywords: birds of prey conservation; illegal killing; pair formation; parental care; Sicily; supplementary feeding